A Characterization of Power Method Transformations through L-Moments. (7th February 2011) - Headrick, Todd C.
Abstract : Power method polynomial transformations are commonly used for simulating continuous nonnormal distributions with specified moments. However, conventional moment-based estimators can (a) be substantially biased, (b) have high variance, or (c) be influenced by outliers. In view of these concerns, a characterization of power method transformations by L -moments is introduced. Specifically, systems of equations are derived for determining coefficients for specified L -moment ratios, which are associated with standard normal and standard logistic-based polynomials of order five and three. Boundaries for L -moment ratios are also derived, and closed-formed formulae are provided for determining if a power method distribution has a valid probability density function. It is demonstrated that L -moment estimators are nearly unbiased and have relatively small variance in the context of the power method. Examples of fitting power method distributions to theoretical and empirical distributions based on the method of L -moments are also provided.